Levensoriëntatie: een inductief waardenonderzoek - van der Zande, Edwin (Religie & Samenleving, 2019)
This article presents a newly developed alternative to mainstream practices in education and in value research. It is a layered model of qualitative research that creates value for education and for research practices. In this article, I claim the necessity for students at a university of applied sciences to develop and articulate their moral consciousness as part of their normative professionalisation. Mainstream educational practice often shows a preference for a deductive approach, for example, in letting students choose three values from a longer list of pre-selected values. Quantitative scientific value research is analogous to this deductive approach and neglects the complexity of a value system as a product of life-long experiences. In this contribution an innovative notion of life orientation is presented, which conceptually emphasises the inductive and processual character of a developing personal and professional value system. Life orientation is an existential positioning process that needs further articulation for fostering moral awareness. In this particular alternative, in which articulation becomes part of an educational approach, students become first-line inquirers of their morality, and it invites them to broaden and deepen their moral vocabulary in relation to their increased awareness. This broadened vocabulary, furthermore, enables them to improve their dialogical competencies, which is beneficial for establishing an informed dialogue among professionals on the moral dimension of their practice. For scientific reasons, the first-line narrative inquiry of students could be subject to further narrative research. Though a narrative-inductive approach is time-consuming, it provides for a rich set of data. The exemplifying narrative of Izzy shows that within a life orientation different, sometimes opposing, views are the components of a developing but complex and contextualising narrative.